Respuesta :

Answer:

[tex] w = 6 [/tex]

Step-by-step explanation:

ST = w + 6,

PR = w

From the diagram given, we can deduce that PR is the midsegment of ∆QST. Therefore, according to the midsegment theorem:

PR = ½ of ST

Plug in the values into the equation and solve for w.

[tex] w = \frac{1}{2}(w + 6) [/tex]

[tex] w = \frac{w}{2} + 3 [/tex] (distributive property of equality)

[tex] w - 3 = \frac{w}{2} [/tex] (subtraction property of equality)

[tex] 2(w - 3) = \frac{w}{2}*2 [/tex] (multiplication property of equality)

[tex] 2w - 6 = w [/tex]

[tex] 2w - 6 - 2w= w - 2w [/tex] (subtraction property of equality)

[tex] - 6 = - w [/tex]

Divide both sides by -1

[tex] 6 = w [/tex]

[tex] w = 6 [/tex]